Identification of a mitophagy-related gene signature for predicting overall survival and response to immunotherapy in rectal cancer - Jian Yang; Zhifei Cao; Chengqing Yu; Wenxu Cui; Jian Zhou (BMC Cancer)
Abstract Background Rectal cancer is a highly heterogeneous gastrointestinal tumor, and the prognosis for patients with treatment-resistant and metastatic rectal cancer remains poor. Mitophagy, a type of selective autophagy that targets mitochondria, plays a role in promoting or inhibiting tumors; however, the importance of mitophagy-related genes (MRGs) in the prognosis and treatment of rectal cancer is unclear. Methods In this study, we used the differentially expressed genes (DEGs) and MRGs from the TCGA-READ dataset to identify differentially expressed mitophagy-related genes (MRDEGs). The mitophagy scores were then analyzed for differential expression and ROC. Seven module genes were identified using the weighted gene coexpression network analysis (WGCNA) approach and subsequently validated in the merged datasets GSE87211 and GSE90627. The model genes were obtained based on prognostic features, and the subgroups were distinguished by risk score. Gene enrichment, immune infiltration and immunotherapy response were also evaluated. Finally, validation of prognostic gene expression in rectal cancer was carried out using clinical samples, employing Immunohistochemistry (IHC). Results We demonstrated that 22 MRGs were differentially expressed between normal and rectal cancer tissues. A prognostic model for rectal cancer MRGs was constructed using WGCNA and Cox regression, which exhibited good diagnostic performance. In this study, we identified four molecular markers (MYLK, FLNC, MYH11, and NEXN) as potential prognostic biomarkers for rectal cancer for the first time. Moreover, our findings indicate that the risk scores derived from the four MRGs are associated with tumor immunity. To further validate our findings, IHC analyses suggested that the expression of MYH11 in rectal cancer tissues was lower than in nontumorous rectal tissues. Conclusion MRGs could predict the prognosis and response to immunotherapy in patients with rectal cancer and might be able to personalize treatment for patients.